(untitled) (Bangladesh Agronomy Journal, 2022)
A field experiment was conducted at the Agronomy field, Sher-e-Bangla Agricultural University, Dhaka to evaluate the effect of water stress at reproductive stage on growth, grain development and yield of Boro rice. The experiment consisted of two factors: Factor A: Water stress viz. no water stress (W1) and water stress (W2) and Factor B: Variety viz. BRRI dhan28 (V1), BRRI dhan29 (V2), BRRI dhan50 (V3), Binadhan-10 (V4), BRRI hybriddhan3 (V5), Aloron (V6). In no water stress, irrigation water was maintained strictly from transplanting time to harvesting time while in water stress condition; supply of irrigation was stopped just after flowering upto harvest. Results showed that growth, grain development and yield of Boro rice were significantly affected by water stressed condition. All the tested varieties performed better under no water stress condition compared to water stress condition. About 7% panicle weight was decreased due to water stress condition at reproductive stage. Grain development of BRRI dhan29 was least affected by water stress while the most affected variety was Binadhan-10. Water deficit at reproductive stage reduced about 15-22% grain yield of tested varieties. Aloron was the least affected variety due to water stress while BRRI dhan50 was the most affected variety. The variety Aloron provided equal yield (7.31 t ha-1) under stress condition as given by BRRI dhan29 under no water stress condition. So, Aloron may be a better option to cultivate in the region where irrigation water is scarce or costly. Bangladesh Agron. J. 2021, 24(2): 99-107